KESEMPURNAAN KONTRAK KERJA KONSTRUKSI MENGHINDARI SENGKETA (Lex Jurnalica, 2016)
AbstractConstruction activity requires a written form of engagement between service users and service providers in the form of a contract or the so-called construction work contract. Construction Work Contract is an important document which contains provisions governing the rights and obligations of both users and providers of construction services to be prepared with care and attention to many aspects, especially its legal aspects. Research using a type of normative research by reviewing the formal law in engagement construction contracts, where research is descriptive analytic by using the data collection tool document study to obtain secondary data sourced from primary legal materials in the form of regulations in construction services, legal materials secondary and tertiary legal materials and the results were analyzed qualitatively. Keywords: Construction work contract, construction services AbstrakKegiatan jasa konstruksi memerlukan suatu bentuk perikatan tertulis antara pengguna jasa dan penyedia jasa yang berbentuk kontrak atau yang disebut dengan kontrak kerja konstruksi. Kontrak Kerja Konstruksi merupakan dokumen penting yang berisi ketentuan yang mengatur hak dan kewajiban pengguna maupun penyedia jasa konstruksi yang harus disusun dengan cermat dan memperhatikan banyak aspek terutama aspek hukum. Penelitian menggunakan tipe penelitian normatif dengan mengkaji hukum formil dalam perikatan kontrak konstruksi, dimana penelitian bersifat deskriptif analistis dengan menggunakan alat pengumpul data studi dokumen untuk memperoleh data sekunder yang bersumber dari bahan hukum primer berupa peraturan perundangan bidang jasa konstruksi, bahan hukum sekunder dan bahan hukum tersier dan hasil penelitian dianalisa secara kualitatif. Kata kunci: Jasa konstruksi, kontrak kerja konstruksi